(untitled) (Indian Journal of Veterinary Pathology, 2025)
Pathology of sheep pox in a Mecheri sheep flock has been described. Six adult sheep carcasses from an organized sheep farm were presented for necropsy. Affected sheep had clinical signs of pyrexia, conjunctivitis, laboured breathing, loss of appetite and raised firm nodules in the hairless areas all over the body. On necropsy, skin over the groin, ventral abdomen and inner thigh revealed multiple, round, firm, elevated grey-coloured nodules. Lung lobes revealed many reddish-brown circular areas. Microscopically, hyperplasia with hydropic degeneration of the lining epithelium was observed in tissues of skin, lip, rumen and reticulum. Eosinophilic intracytoplasmic inclusions also seen in hyperplastic epithelial cells of the above tissues. Trachea showed mucosal congestion with subacute tracheitis, epithelial hyperplasia with intracytoplasmic inclusions and lungs showed interstitial pneumonia. Tissues with lesions were subjected to polymerase chain reaction and were found to be positive for ITRs of the sheep pox virus with an amplicon size of 289 bp. The disease was diagnosed as sheep pox on the basis of gross pathology, histopathology and confirmation by molecular methods.